Evolutionary Formation and Distribution of Puumala Virus Genome Variants, Russia - Ekaterina Blinova; Andrei Deviatkin; Marat Makenov; Yulia Popova; Tamara Dzagurova (Emerging Infectious Diseases, 2023)
We analyzed Puumala virus (PUUV) sequences collected from bank voles from different regions of Russia. Phylogenetic analysis revealed PUUV reassortments in areas with the highest hemorrhagic fever with renal syndrome incidence, indicating reassortment might contribute to pathogenic properties of PUUV. Continued surveillance is needed to assess PUUV pathogenicity in Russia.